2007
DOI: 10.1021/la702132t
|View full text |Cite
|
Sign up to set email alerts
|

Nonsolvents Cause Swelling at the Interface with Poly(methyl methacrylate) Films

Abstract: Density profiles of a perdeuterated poly(methyl methacrylate) (dPMMA) film spin-coated on a substrate in water, hexane, and methanol, which are "nonsolvents" for dPMMA, were examined along the direction normal to the interface by specular neutron reflectivity (NR). The interfaces of dPMMA with the liquids were diffuse in comparison with the pristine interface with air; the interfacial width with water was thicker than that with hexane. Interestingly, in water, the dPMMA film was composed of a swollen layer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 44 publications
12
104
2
Order By: Relevance
“…On the other hand, in the WF method, a floating PS film on a water surface was skimmed off by the PMMAcoated silicon wafer from the water side. Here, the PMMA film was once dipped in water and swollen by uptaking water molecules [6] . The floating PS film was provided by peeling off a spin-cast PS film from a Si wafer on a water surface.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, in the WF method, a floating PS film on a water surface was skimmed off by the PMMAcoated silicon wafer from the water side. Here, the PMMA film was once dipped in water and swollen by uptaking water molecules [6] . The floating PS film was provided by peeling off a spin-cast PS film from a Si wafer on a water surface.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, diameters of 1.1 and 1.2 mm were observed in the cases of PHEMA and PFA-C 8 . Tanaka et al 34 have investigated the interfaces between deuterated PMMA (dPMMA) film and poor or nonsolvents by neutron reflectivity and AFM. Although water is a typical nonsolvent for dPMMA, the liquid/solid interfaces were diffuse in comparison with the interface between air and dPMMA.…”
Section: Surface Modification Of the Electrospun Non-woven Fiber Matsmentioning
confidence: 99%
“…The solvent or monomer molecules might penetrate further into the polymer chains at a surface with a large roughness factor than at a smooth surface; the monomers may then polymerize from the inside. 34 The fibers inside the PMMA-co-PBIEM may have been swelled by the solvent or monomer. The fiber was swelled in a concentric circle, whereas the swelling area of the spin-coated film expanded in a perpendicular direction.…”
Section: Surface Modification Of the Electrospun Non-woven Fiber Matsmentioning
confidence: 99%
“…9,10 In other words, the films' outermost surface of waterinsoluble polymers such as poly(methyl methacrylate) (PMMA) tends to swell with water molecules, thus forming 'soft' interfaces. Neutron reflectivity measurements have recently suggested that the thickness of the water-swollen layers of atactic (at) (in fact, syndiotactic (st)-rich) PMMA films was more than 8 nm from the outermost surface.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron reflectivity measurements have recently suggested that the thickness of the water-swollen layers of atactic (at) (in fact, syndiotactic (st)-rich) PMMA films was more than 8 nm from the outermost surface. 9 It has also been suggested that the water-swollen layers of isotactic (it)-PMMA might be thicker than that of atactic-PMMA. 10 Therefore, considering the functional modification of PMMA surfaces using short peptides (for example, the length of 10-mer peptides with an extended chain conformation is expected to be less than 4 nm), the peptides on the PMMA film surfaces might be embedded inside the water-swollen layers, and would not function as surface modifiers (Figure 1, top).…”
Section: Introductionmentioning
confidence: 99%